2021
DOI: 10.1002/cac2.12182
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic regulation in the immune response to cancer

Abstract: Metabolic reprogramming in tumor‐immune interactions is emerging as a key factor affecting pro‐inflammatory carcinogenic effects and anticancer immune responses. Therefore, dysregulated metabolites and their regulators affect both cancer progression and therapeutic response. Here, we describe the molecular mechanisms through which microenvironmental, systemic, and microbial metabolites potentially influence the host immune response to mediate malignant progression and therapeutic intervention. We summarized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 291 publications
(378 reference statements)
0
24
0
Order By: Relevance
“…These immune cells obviously adapt to the regional environment and show metabolic characteristics analogous to those of resident tissue. 171 , 172 In parallel, several immune cell subsets and multitudinous immunological factors dynamically exist in circulation and migrate throughout the body to conduct immunosurveillance. When at rest, these immune cells commonly need few nutrients.…”
Section: Nutrient-associated Molecular Mechanismsmentioning
confidence: 99%
“…These immune cells obviously adapt to the regional environment and show metabolic characteristics analogous to those of resident tissue. 171 , 172 In parallel, several immune cell subsets and multitudinous immunological factors dynamically exist in circulation and migrate throughout the body to conduct immunosurveillance. When at rest, these immune cells commonly need few nutrients.…”
Section: Nutrient-associated Molecular Mechanismsmentioning
confidence: 99%
“…Aging is a major problem facing mankind, and the pursuit of immortality is an eternal topic [111][112][113][114]. After more and more studies, mesenchymal stem cells have been found to play a great role in combating aging.…”
Section: The Anti-aging Effect Of Mscsmentioning
confidence: 99%
“…In this way, onco-spheres can be classified among niches where tumor initiates, expands and spreads, namely the primary, regional (lymph nodes), distal (pre/postmetastatic) as well as systemic onco-spheres accordingly (Figure 1). Employing the principles of ecology, cancer cells act as the emerging species that employ different metabolic and reproductive strategies to hijack resources and space from the existing host cells, evade/defense predation by the host immunity, and cooperate to disperse throughout the circulation, followed by co-evolution with new oncospheres and end up colonizing as macroscopic outgrowths [8]. Three essential factors are critical for the onco-sphere formation: energy source, microenvironment, and interactive network.…”
Section: Introductionmentioning
confidence: 99%